059 HSV1 Encephalitis as a postoperative complication of neurosurgical intervention. Issue 3 (9th February 2012) - Ali, K; Prevett, M; Pelosi, E
Abstract : Intracranial infections following neurosurgery are most commonly caused by bacteria. Postoperative herpes simplex encephalitis has been described but rarely. A 71-year-old woman was admitted electively for resection of a recurrent benign posterior fossa tumour. The operation went without immediate complications and the patient seemed to be doing well in the initial postoperative phase. At day nine postoperatively, she developed a fever associated with acute confusion and altered behaviour. On examination she was febrile with a GCS of 10/15. There was no focal neurological deficit and general examination was normal. CSF examination showed a glucose of 1 mmol/l (plasma glucose 7) with a CSF protein of 8 g, 330 lymphocytes and no RBCs. No bacteria were seen and cultures were negative, but HSV1 PCR was positive. CT Brain showed ventricular enlargement; MRI showed a small medullary infarct and postoperative change. The patient was treated with acyclovir and an EVD was inserted. Serial CSF examination showed persistently positive HSV1 PCR. 3 weeks later, Foscarnet was added for 2 weeks. The EVD was subsequently removed and the antivirals stopped. The patient's clinical condition remained stable with significant neurological disability. There are only 10 case reports of postoperative HSV1 encephalitis. These reports suggest that this rare postoperative complication is associated with a poor prognosis, with high mortality and morbidity. Neurosurgical interventions involving peripheral nerve root or ganglia have been reported to cause re-activation of cutaneous herpes simplex infection. Factors compromising the immune system may also increase susceptibility to herpes simplex infection.